2013
DOI: 10.1002/bltj.21575
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Subscriber Churn Using Social Network Analysis

Abstract: In today's world, mobile phone penetration has reached a saturation point. As a result, subscriber churn has become an important issue for mobile operators as subscribers switch operators for a variety of reasons. Mobile operators typically employ churn prediction algorithms based on service usage metrics, network performance indicators, and traditional demographic information. A newly emerging technique is the use of social network analysis (SNA) to identify potential churners. Intuitively, a subscriber who i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 20 publications
0
34
0
3
Order By: Relevance
“…The primary application is to use a model in order to improve the service of OSN [9]. Telecoms are trying to detect possible churners (users that are likely to change network) by analysing social network where a stronger link or tie means a greater influence between users [18][19][20]. Usually information for building that kind of social network is fetched from call detail records (CDR).…”
Section: Related Work and Motivationmentioning
confidence: 99%
“…The primary application is to use a model in order to improve the service of OSN [9]. Telecoms are trying to detect possible churners (users that are likely to change network) by analysing social network where a stronger link or tie means a greater influence between users [18][19][20]. Usually information for building that kind of social network is fetched from call detail records (CDR).…”
Section: Related Work and Motivationmentioning
confidence: 99%
“…A churn prediction algorithm that quantifies the strength of social ties, which are defined by means of several parameters, is presented in [28]. Later on, over this scenario, the authors apply a diffusion model to assess the influence of churners.…”
Section: Social Churning Predictionmentioning
confidence: 99%
“…In [26] is argued that churn is an event due to personal decisions and outlines, and of course, it is affected by external occurrences and, among them, by the impacts of the community where this individual belongs. In [28], the authors present an approach that takes into account intrinsic and extrinsic factors, using the idea of Collective Classification (CC). With this in mind, we decided it was important that the proposed model took into account social behavior.…”
Section: Social Networkmentioning
confidence: 99%
“…In business-oriented contexts, where costs and benefits are a concern, it is furthermore valuable to detect the potential churners early enough for the campaigns to achieve optimal success and maximize their return (Verbraken et al, 2013). Research has shown that features that incorporate the influence of prior churners in a customer's social circle -their ego-net-are usually good predictors of churn when it is treated as a binary classification problem (Óskarsdóttir et al, 2017;Verbeke et al, 2014;Phadke et al, 2013). These features are extracted from call networks which are constructed based on call detail records (CDR) by linking together customers who have called or texted each other.…”
Section: Introductionmentioning
confidence: 99%